1979
DOI: 10.1079/bjn19790058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biochemical and clinical indices of B-vitamin deficiency. A study in rural school boys

Abstract: I . A study amongst schoolboys in villages around Hyderabad, India, showed that almost all the boys had riboflavin deficiency, 61 % had pyridoxine deficiency, and 9'4% had thiamin deficiency as judged by enzymic tests.2. The prevalence of angular stomatitis was 41.3 yo and that of glossitis was 18.2 %. Biochemical deficiency of riboflavin and pyridoxine was marginally higher in children with angular stomatitis with or without associated glossitis, than in children without oral lesions.3. Treatment with B-compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 10 publications
3
13
0
1
Order By: Relevance
“…These data may explain the much higher prevalence of biochemical riboflavin defi ciency compared to that of the other B com plex vitamins such as thiamine, pyridoxine and folic acid observed in our earlier studies [1][2][3][4][5]. The perplexing lack of clear-cut corre lation between biochemical and clinical le sions of riboflavin deficiency reported by us [2][3][4] and other workers [17,18] may also be explained by the artefactual changes in the riboflavin levels of blood or urine under above-mentioned conditions.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These data may explain the much higher prevalence of biochemical riboflavin defi ciency compared to that of the other B com plex vitamins such as thiamine, pyridoxine and folic acid observed in our earlier studies [1][2][3][4][5]. The perplexing lack of clear-cut corre lation between biochemical and clinical le sions of riboflavin deficiency reported by us [2][3][4] and other workers [17,18] may also be explained by the artefactual changes in the riboflavin levels of blood or urine under above-mentioned conditions.…”
Section: Discussionmentioning
confidence: 82%
“…Thus when rural school children were supplemented daily with B complex vitamins containing 4 mg ribo flavin for 1 month, or 1.5 mg riboflavin for 1 year, only 50% showed normal riboflavin status as judged by the values for erythrocyte glutathione reductase (EGR) activity (EC 1.6.4.2), and its in vitro stimulation with FAD [3,4). The remaining 50% had im proved but not normalized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be another limitation of the study. Angular stomatitis may be due to infections when it responds to topical applications of antibiotics or gentian violet, as in earlier studies (Bamji et al, 1979) or due to micronutrient deficiencies (Blanck et al, 2002). Since in our study angular stomatitis disappeared when fortified salt was used, it may be assumed that the cause of angular stomatitis in our study might have been micronutrient deficiencies and not infections.…”
Section: Discussionmentioning
confidence: 55%
“…Studies on women and children in devel oping countries have revealed a very high incidence of biochemical riboflavin defi ciency as judged by the activation of eryhtrocyte glutathione reductase (EGR) with its co enzyme flavin adenine dinucleotide (FAD, EGR activation coefficient, AC) [1][2][3][4][5]. While the diets of these people are generally deficient in riboflavin, supplementation with riboflavin does not always normalize biochemical deficiency suggesting involve ment of non-dietary factors as well, in the causation of riboflavin deficiency.…”
Section: Introductionmentioning
confidence: 99%